2020
DOI: 10.1186/s12885-020-06998-9
|View full text |Cite
|
Sign up to set email alerts
|

Histologic subtyping affecting outcome of triple negative breast cancer: a large Sardinian population-based analysis

Abstract: Background Triple Negative breast cancer (TNBC) includes a heterogeneous group of tumors with different clinico-pathological features, molecular alterations and treatment responsivity. Our aim was to evaluate the clinico-pathological heterogeneity and prognostic significance of TNBC histologic variants, comparing “special types” to high-grade invasive breast carcinomas of no special type (IBC-NST). Methods This study was performed on data obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 53 publications
2
19
0
Order By: Relevance
“…In a study by Francesca et al, triple negative ILC showed the worst survival outcomes (79.7% at 5-years and 73.8% at 10-years) among all histological types. The same study reported that triple negative ILC showed a higher metastatic lymph node ratio (> 0.65) and lower response to chemotherapy than those of other triple negative breast cancer histological types [ 20 ]. It is hard to predict outcomes based on current classification and treatment regimens because the ER−/PR− population shows heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Francesca et al, triple negative ILC showed the worst survival outcomes (79.7% at 5-years and 73.8% at 10-years) among all histological types. The same study reported that triple negative ILC showed a higher metastatic lymph node ratio (> 0.65) and lower response to chemotherapy than those of other triple negative breast cancer histological types [ 20 ]. It is hard to predict outcomes based on current classification and treatment regimens because the ER−/PR− population shows heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…The IM subtype is enhanced in immune cell processes (cell and cytokine signaling, antigen processing, and presentation) and signaling by transduction of the immune signal of the nucleus. IM GO overlaps with a gene signature for medullary BC, an unusual, high-grade histologic TNBC subtype showing favorable prognosis [7,28]. The M and MSL subtype GOs are enriched in cell motility, extracellular matrix (ECM) receptor interaction, and cell differentiation.…”
Section: Molecular Classifications Of Tnbc: Clinical Outcome Implicatmentioning
confidence: 99%
“…TNBC shows different molecular and clinicopathological features [6] and is histologically categorized as a high-grade invasive BC of no special type. "Special types" are still included into the TNBC subtype but differ in biological behavior and clinical course [7].…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer (BC) is a heterogeneous disease enclosing several entities with different morphologic, prognostic and therapeutic features [ 1 ]. Invasive breast cancer is classified according to histology and immunohistochemistry (i.e., ER, PR, HER2 overexpression, and/or HER2 gene amplification, and Ki67 proliferation index) [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer (BC) is a heterogeneous disease enclosing several entities with different morphologic, prognostic and therapeutic features [ 1 ]. Invasive breast cancer is classified according to histology and immunohistochemistry (i.e., ER, PR, HER2 overexpression, and/or HER2 gene amplification, and Ki67 proliferation index) [ 1 , 2 ]. Surrogate molecular classification of BC by means of immunohistochemistry defines specific subtypes, such as Luminal A (ER and PR positive, HER2 negative, low Ki67), Luminal B (ER positive, PR positive/negative, HER2 negative, high Ki67), Luminal B HER2+ (ER positive, PR positive/negative, HER2 positive, any Ki67), HER2+ non-luminal (ER-PR negative, HER2 positive, high Ki67), and triple negative (ER-PR-HER2 negative, high Ki67) [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%